2000
DOI: 10.1128/aac.44.6.1645-1649.2000
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Antimalarial Activity of the Beta-Carboline Alkaloid Manzamine A

Abstract: Manzamine A, a ␤-carboline alkaloid present in several marine sponge species, inhibits the growth of the rodent malaria parasite Plasmodium berghei in vivo. More than 90% of the asexual erythrocytic stages of P. berghei were inhibited after a single intraperitoneal injection of manzamine A into infected mice. A remarkable aspect of manzamine A treatment is its ability to prolong the survival of highly parasitemic mice, with 40% recovery 60 days after a single injection. Oral administration of an oil suspension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 213 publications
(140 citation statements)
references
References 17 publications
2
136
0
1
Order By: Relevance
“…8 Although compounds 3 and 5 were inactive against malaria and leishmania, these results provide valuable information on the structural moieties required for activity against malaria and leishmania. This observation further supports our previous report 4 which indicates that reduction of the C32-C33 olefin and oxidation of C-31 also significantly reduces the antimalarial activity for the manzamine alkaloids in vivo. These data combined strongly suggest that the ability of the C-34 allyliccarbon to form a stabilized carbocation after oxidation both in cell culture and in animals followed by the inherent nucleophilic attack may play a critical role in the biological activity of the manzamine alkaloids against the malarial parasite.…”
Section: Resultssupporting
confidence: 92%
“…8 Although compounds 3 and 5 were inactive against malaria and leishmania, these results provide valuable information on the structural moieties required for activity against malaria and leishmania. This observation further supports our previous report 4 which indicates that reduction of the C32-C33 olefin and oxidation of C-31 also significantly reduces the antimalarial activity for the manzamine alkaloids in vivo. These data combined strongly suggest that the ability of the C-34 allyliccarbon to form a stabilized carbocation after oxidation both in cell culture and in animals followed by the inherent nucleophilic attack may play a critical role in the biological activity of the manzamine alkaloids against the malarial parasite.…”
Section: Resultssupporting
confidence: 92%
“…The 3 J coupling of H-37 and H-22 (δ 3.75) in the COSY spectrum indicated that the 2-ketopropyl group was connected to C-22. Additional significant evidence for the structure was provided by the natural abundance 1 H- 15 3 , although it may not be the preferred conformation in energy level. This will no doubt be helpful in future SAR studies, since the ligand-based drug design takes solvent effects into consideration.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…A gradient HMBC pulse sequence with 1 ms Gaussian Z-axis gradient pulses (70:30:50) was used. Referencing of the indirectly detected 15 N dimension was accomplished using nitromethane as an external standard. A GHMBC experiment was performed with nitromethane, and the 15 N correlation was calibrated to 380.2 ppm.…”
Section: N Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…10 As part of our ongoing investigations to identify new manzamines and to define the SAR as well as utilize the natural products as synthetic starting materials, [1][2][3][11][12][13] extracts of the Indonesian sponge Acanthostrongylophora sp. were investigated.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%